Transforming Discipleship: Missional church, discipleship and the discourse of transformation amongst the urban poor - Njuguna, Daniel (Ecclesial Futures, 2021)
Bevans’ concept of transforming discipleship foregrounds a fundamental symbiotic relationship between discipleship and mission. The interplay between both practices is central to the wider debate of contemporary church social engagement under missio Dei. He explains that the notion of baptism and theosis embedded in the idea of transforming discipleship points to a concrete transformation of the human experience and condition. This forms the premise of this article in exploring how Christian practices of discipleship and mission articulate a process of human becoming and participation in the life and mission of God that centres on a critical engagement with lived reality. This understanding offers a consistent framework of fostering a mutual relationship between local churches and communities in the poorer urban context, which often face the twin challenge of church and social decline. It questions a simplistic binary correlation between the practices of discipleship and mission. Such correlation often leads to a seeming dichotomy in Christian practices, with mission being portrayed as a means of achieving a quantitative outcome and discipleship a qualitative one. Instead, the focus of this article is to elucidate how discipleship and mission are interwoven, that both start with God and are integral to the actualisation of God’s salvific plan in the world.